Spatiotemporal analysis of atmospheric XCH4 as related to fires in the Amazon biome during 2015–2020 - de Souza Maria, Luciano [UNESP]; Rossi, Fernando Saragosa [UNESP]; Costa, Luis Miguel da [UNESP]; Campos, Marcelo Odorizzi [UNESP]; Blas, Juan Carlos Guerra [UNESP]; Panosso, Alan Rodrigo [UNESP]; Silva, Joao Lucas Della; Silva Junior, Carlos Antonio da; La Scala Jr, Newton [UNESP] (Elsevier, 2023)
Studies that focus on the concentration of methane and its relationship with fires in the Amazon have become relevant in the current scenario, especially due to the increasing environmental degradation associated with climate change. Therefore, the main objective of the study was to investigate the spatial–temporal variability in the observations of XCH4 in the time series of 2015 a 2020 and understand the correlations between XCH4 and the fire foci number, CO2 anomalies and biophysical variables (temperature and soil moisture) under the Amazon biome. For number of active fires foci (Fire Foci) and Land Surface Temperature (LST) were obtained through the Moderate Resolution Imaging Spectroradiometer (MODIS) sensor, and the atmospheric concentrations of the averaged column of methane (XCH4) and carbon dioxide (XCO2) were obtained by the Greenhouse gases Observing SATellite (GOSAT) satellites and Orbiting Carbon Observatory-2 (OCO-2), respectively. The Soil Moisture (SMAP) was obtained through satellite Soil Moisture Active Passive (SMAP). The analysis was carried out in the dry and wet seasons, and the XCH4 presented an annual mean and standard error of 1794 ± 5.3 ppb for the rainy season, while for the dry period, the XCH4 was 1789 ± 5.6 ppb. For the spatial distribution of XCH4, a significant correlation (r = 0.53 and p < 0.05) was observed between XCH4 and Anomaly XCO2 in the dry season, possibly justified by the increase in fire foci. Additionally, in the dry period, XCH4 was significantly correlated with SMAP (r = 0.97, p < 0.01), validating the hypothesis of a strong relationship between the variables. The temporal variability of XCH4 was significant for SMAP (r = 0.65 and p < 0.01), similar to the significance of the LST variable (r = 0.66 and p < 0.01). Thus, the temporal distribution of XCH4 was positively related to both soil moisture and land surface temperature. Therefore, considering more frequent droughts and the predominance of fires in the region, as well as the increase in global average temperature, there will be an increase in greenhouse gas (GHG) emissions, especially methane, further impacting the Amazonian ecosystem, which is already vulnerable to climate change.
Keywords: Arc of deforestation; Climate changes; Fire foci; Seasonality; Soil moisture; XCO2